2015
DOI: 10.1177/000313481508100410
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Cysts

Abstract: Brief Reports should be submitted online to www.editorialmanager.com/ amsurg. (See details online under ''Instructions for Authors''.) They should be no more than 4 double-spaced pages with no Abstract or sub-headings, with a maximum of four (4) references. If figures are included, they should be limited to two (2). The cost of printing color figures is the responsibility of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Therefore, in the differential diagnosis of PCs, one must consider thyroid goiter, thyroid cyst, thymic cyst, thyroid adenoma, and parathyroid carcinoma. [ 2 , 6 , 10 , 50 , 57 , 125 , 143 , 152 , 162 – 173 ] Furthermore, thyroglossal duct cyst and branchial cleft cyst should be taken into consideration as neck masses that usually mimic PCs. Multiple studies support the assumption that test of the cystic fluid aspirated by FNA is the best method to distinguish PCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in the differential diagnosis of PCs, one must consider thyroid goiter, thyroid cyst, thymic cyst, thyroid adenoma, and parathyroid carcinoma. [ 2 , 6 , 10 , 50 , 57 , 125 , 143 , 152 , 162 – 173 ] Furthermore, thyroglossal duct cyst and branchial cleft cyst should be taken into consideration as neck masses that usually mimic PCs. Multiple studies support the assumption that test of the cystic fluid aspirated by FNA is the best method to distinguish PCs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 , 111 , 147 , 196 – 199 ] This pathology refers mainly to nonfunctioning cysts, whereas functioning ones lack this epithelium and are characterized more as pseudocysts. [ 2 , 92 , 131 , 200 ] Kuo et al [ 201 ] reported a case of an adenoma found lined in the cyst wall, surrounded by cyboid cells. References in the literature reveal that hyperfunctioning PCs can be formed by adenomatous tissue without any evidence of adenoma or hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best treatment for FPC is surgical removal of the lesion, but for NFPC, surgical treatment is optional. There are three options for the treatment of NFPC including simple aspiration, percutaneous sclerosing agent injections and surgical resection [ 4 , 5 ]. Ultrasound-guided aspiration can be used alone as an initial treatment for symptomatic NFPCs, and it can immediately resolve compression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…They are often mistaken for other neck masses, such as thyroid cysts. There are three options for treatment of PC: aspiration, percutaneous injection of sclerosing agents, and surgical resection [ 4 , 5 ]. At present, the diagnosis and treatment of PC is limited to a few small case reports.…”
Section: Introductionmentioning
confidence: 99%